New reactivity and selectivity in rhodium-catalysed hydroacylation - Pal, R (2020)
This thesis documents the development of two new rhodium(I)-catalysed methodologies. The first shows the use of 1,4-dicarbonyl systems in hydroacylation for the preparation of synthetically valuable alpha-N-amido ketones. The second method is a dynamic kinetic resolution process for the synthesis of enantiomerically enriched 1,3-dicarbonyl compounds.